The complete mitochondrial genome of Echinoecus nipponicus Miyake, 1939 (Crustacea: Decapoda: Pilumnidae), a symbiont of sea urchins - Sang-Hui Lee; Taeg Kwan Oh; Myung-Hwa Shin (Mitochondrial DNA. Part B. Resources, 2018)
The mitochondrial genome of a crab symbiotic with sea urchins, Echinoecus nipponicus, was completely sequenced for the first time. The total mitogenome length of E. nipponicus was 16,173 bp including 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. The phylogenetic tree confirmed that E. nipponicus belonged to the subsection Heterotremata within Brachyura. This is the first record of the complete mitogenome for the subfamily Eumedoninae.